Construcción de una escala de autoeficacia para comunicación oral y escrita dentro de entornos laborales en futuros egresados (2021)
The current job market needs workers with adequate levels of transversal skills such as communication abilities. In this sense, self- efficacy becomes relevant, since this constitutes a factor in the achievement of goals of an individual, so it is necessary to evaluate it in future graduates (n=443) using valid and reliable scales. To this aim, a scale for measure self-efficacy for communication within work environments was validated and it’s reliability calculated. To obtain the validity of content, the CVI method was used, and for internal consistency, the Spearman-Brown method was applied as well as Cronbach’s alpha coefficient. A factorial analysis was made to obtain construct validity. Results shows, high levels of CVI (.87) and internal consistency (R = .94, α = .93). Also, four factorsthat explain the 66 % of variance were obtained. The instrument is valid and reliable to measure self-efficacy for communication within workenvironments in future graduates.